Early childhood diarrhoeal diseases and cognition: are we missing the rest of the iceberg?. (November 2014) - MacIntyre, Jessica; McTaggart, Jennifer; Guerrant, Richard L.; Goldfarb, David M.
Abstract : Risk factors which interfere with cognitive function are especially important during the first 2 years of life – a period referred to as early child development and a time during which rapid growth and essential development occur. Malnutrition, a condition whose effect on cognitive function is well known, has been shown to be part of a vicious cycle with diarrhoeal diseases, and the two pathologies together continue to be the leading cause of illness and death in young children in developing countries. This paper reviews the burden of early childhood diarrhoeal diseases globally and the emerging evidence of their relationship with global disparities in neurocognitive development. The strength of evidence which indicates that the severe childhood diarrhoeal burden may be implicated in cognitive impairment of children from low- and middle-income counties is discussed. Findings suggest that greater investment in multi-site, longitudinal enteric infection studies that assess long-term repercussions are warranted. Furthermore, economic analyses using the concept of human capital should play a key role in advancing our understanding of the breadth and complexities of the health, social and economic ramifications of early childhood diarrhoeal diseases and enteric infections. This broadened awareness can serve to help advocate for more effective interventions, particularly in developing economies.